Impact of Repeated Stress on Traumatic Brain Injury-Induced Mitochondrial Electron Transport Chain Expression and Behavioral Responses in Rats - Xing, Guoqiang; Barry, Erin S.; Benford, Brandi; Grunberg, Neil E.; Li, He; Watson, William D.; Sharma, Pushpa (Frontiers in Neurology, 2013)
A significant proportion of the military personnel returning from Iraq and Afghanistan conflicts have suffered from both mild traumatic brain injury (mTBI) and post-traumatic stress disorder (PTSD). The mechanisms are unknown. We used a rat model of repeated stress and mTBI to examine brain activity and behavioral function. Adult male Sprague-Dawley rats were divided into 4 groups: Naïve; 3 days repeated tail-shock stress; lateral fluid percussion mTBI; and repeated stress followed by mTBI (S-mTBI). Open field activity, sensorimotor responses, and acoustic startle responses were measured after mTBI. The protein expression of mitochondrial electron transport chain (ETC) complex subunits (CI-V) and pyruvate dehydrogenase (PDHE1α1) were determined in 4 brain regions at day 7 post mTBI. Compared to Naïves, repeated stress decreased horizontal activity; repeated stress and mTBI both decreased vertical activity; and the mTBI and S-mTBI groups were impaired in sensorimotor and acoustic startle responses. Repeated stress significantly increased CI, CII, and CIII protein levels in the prefrontal cortex (PFC), but decreased PDHE1α1 protein in the PFC and cerebellum, and decreased CIV protein in the hippocampus. The mTBI treatment decreased CV protein levels in the ipsilateral hippocampus. The S-mTBI treatment resulted in increased CII, CIII, CIV, and CV protein levels in the PFC, increased CI level in the cerebellum, and increased CIII and CV levels in the cerebral cortex, but decreased CI, CII, CIV, and PDHE1α1 protein levels in the hippocampus. Thus, repeated stress or mTBI alone differentially altered ETC expression in heterogeneous brain regions. Repeated stress followed by mTBI had synergistic effects on brain ETC expression, and resulted in more severe behavioral deficits. These results suggest that repeated stress could have contributed to the high incidence of long-term neurologic and neuropsychiatric morbidity in military personnel with or without mTBI.